Film Policy and the Role of Lithuanian Film Studio, Riga Film Studio and Tallinnfilm in Developing National Film Production - Dabrovolskas, Audrius (Information & Media, 2022)
National film production in newly developing film industries in Europe, such as in Lithuanian, Latvian and Estonian, did not receive much attention. This article analyzes the concept of national cinema, its connection with film policy in European film industries and the Baltic film industries as well as the role of the biggest film studios in Lithuania, Latvia and Estonia in producing and developing national film production.
Keywords: Film production; national films; film policy; film studios; Baltic film industries